Meningioma of Foramen Magnum Causing Drop Attacks - Amit Mahore; Raghvendra Ramdasi; Sandip Mavani; Vithal Rangarajan; Manoj Patil; Prashant Sathe; Juhi Kawale; Vishakha Tikeykar (Case Reports in Neurological Medicine)
A 52-year-old female presented with frequent episodes of falls without loss of consciousness. These episodes lasted for brief period followed by full neurological recovery. Magnetic resonance imaging (MRI) of the brain showed foramen magnum meningioma encasing left vertebral artery. The patient had dramatic improvement after excision of the tumor.